Do university students’ quality of learning engagement behaviour matter? An empirical insight / Lennora Putit ... [et al.] - Putit, Lennora; Sheriff, Siti Halijjah; Kamarul Zaman, Maliza Delima; Andaleeb, Syed Saad; Bhuiyan, Serajul I (Universiti Teknologi MARA, 2022)
Past research demonstrates that quality and value of a tertiary education have been continuously scrutinized by various relevant stakeholders within the global higher education community to ensure effective scholarship of engagement amongst university students. Drawing from the Theory of Planned Behaviour (TPB), this study aims to examine the extent to which psychological factors such as attitude towards learning, lecturers’ teaching influences as well as perceived behavioural control on knowledge and skills, affect university students’ quality of learning engagement behaviour. A quantitative research design was applied by using a quota sampling technique. From the three hundred (300) survey questionnaires distributed to the undergraduate students, only two hundred and eightyeight (288) returned feedbacks were usable and subsequently tested for further data analyses using both Statistical Package for the Social Sciences (SPSS) version 23.0 and Smart Partial Least Squares 3.0 Structural Equation Modelling (PLS-SEM) statistical software. Empirical results revealed significant influences of both undergraduate students’ attitude and perceived behavioural control on the quality of learning engagement behaviour. Several theoretical and managerial implications were further discussed in this study.